Congenital Internal Jugular Phlebectasia: An Anomaly Still Poorly Recognized - Alessandro Raffaele; Marta Gazzaneo; Piero Romano; Maria Sole Prevedoni Gorone; Luigi Avolio (European Journal of Pediatric Surgery Reports, 2023)
Congenital internal jugular phlebectasia (CIJP) is a rare condition characterized by congenital dilatation of the vein without tortuosity that becomes more evident during straining as a lateral neck mass. CIJP often remains undiagnosed from a few months to several years after the onset of the swelling. It is frequently asymptomatic although symptomatic cases have been occasionally reported. We present the case of a healthy 7-year-old boy with a lateral neck mass, triggered by the Valsalva maneuver. Neck ultrasound (US) showed right internal jugular axial ectasia, increasing during the Valsalva maneuver; contrast computed tomography (CT) scan confirmed a fusiform dilatation of the right internal jugular vein. Due to the lack of symptoms, we treated our patient conservatively. At 5 years of follow-up, the patient is still asymptomatic, with no evidence of complications or thrombosis. Due to its self-limiting nature, treatment for asymptomatic cases of CIJP should be conservative, providing a follow-up with both clinical and US annual evaluations.